Pengoptimalisasian Persediaan Dengan Menggunakan Sistem Distribution Requirement Planning (DRP) di PT. XYZ - Anggit Suryopratomo; kiki abdul muluk (Sainteks: Jurnal Sain dan Teknik, 2022)
Most of the Indonesian population has a livelihood in agriculture. Fertilizer is the main component for farmers to use in farming so that managed plants can grow well. PT XYZ must be able to provide fertilizer in accordance with the demands and needs of local farmers. The level of fertilizer inventory in the warehouse is analyzed and recommendations are given to make it optimal. Optimal in the sense that the inventory level does not experience a shortage of inventory. The research method in the case study at PT XYZ is descriptive analytic. The data collection techniques used were observation, interviews and documentation studies obtained from companies and literatures related to writing. These data were analyzed using qualitative and quantitative analysis. The results obtained from this study with the DRP design using the Q System method, indicate that the estimation that has been made by PT XYZ is the estimate that is closest to the realization in an effort to optimize inventory.